2015
DOI: 10.1021/acs.inorgchem.5b00939
|View full text |Cite
|
Sign up to set email alerts
|

Metallophilic Contacts in 2-C6F4PPh2Bridged Heterobinuclear Complexes: A Crystallographic and Computational Study

Abstract: Treatment of the bis(chelate) complex trans-[Pd(κ(2)-2-C6F4PPh2)2] (7) with PMe3 gave trans-[Pd(κC-2-C6F4PPh2)2(PMe3)2] (13) as a mixture of syn- and anti-isomers. Reaction of 13 with CuCl, AgCl, or [AuCl(tht)] (tht = tetrahydrothiophene) gave the heterobinuclear complexes [(Me3P)2Pd(μ-2-C6F4PPh2)2MCl] [M = Cu (14), Ag (15), Au (16)], from which the corresponding salts [(Me3P)2Pd(μ-2-C6F4PPh2)2M]PF6 [M = Cu (17), Ag (18), Au (19)] could be prepared by abstraction of the chloro ligand with TlPF6; 18, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 58 publications
6
23
0
Order By: Relevance
“…The gold phosphorous distances in 4 (Au−P1 2.3069(13), Au−P2 2.3212(14) Å) are shorter in comparison to the silver phosphorous bond distances in 3 (Ag−P1 2.3818(9), Ag−P2 2.3994(9) Å), yet slightly longer than those in 2 (Au1−P1 2.2724(7), Au2−P2 2.2793(7) Å). The obtained data of both structures is in line with comparable bis‐triarylphosphine complexes of Ag I and Au I …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The gold phosphorous distances in 4 (Au−P1 2.3069(13), Au−P2 2.3212(14) Å) are shorter in comparison to the silver phosphorous bond distances in 3 (Ag−P1 2.3818(9), Ag−P2 2.3994(9) Å), yet slightly longer than those in 2 (Au1−P1 2.2724(7), Au2−P2 2.2793(7) Å). The obtained data of both structures is in line with comparable bis‐triarylphosphine complexes of Ag I and Au I …”
Section: Resultssupporting
confidence: 86%
“…The obtained data of both structuresi sinline with comparable bis-triarylphosphine complexes of Ag I and Au I . [57][58][59] Furthermore,t he isostructural compounds 3 and 4 werei nvestigated by NMR andI Rs pectroscopy. In the 31 P{ 1 H} NMR spectrum( CDCl 3 )o fAu I compound 4 asingle resonance, significantly downfield shifted compared to ligand 1 (d = À14.5 ppm), is detected at d = 34.5 ppm, indicating asole symmetric phosphine gold interaction.…”
Section: Two-foldcoordinationmentioning
confidence: 99%
“…Since that seminal study, a number of complexes have been reported for systems with M = Pd II , Pt II and M' = Au I , Ag I , Cu I , [4][5][6][7][8][9][10][11][12] containing Pd-Au interactions that resemble, more or less closely, the M-M' interactions proposed in reference 1 for the intermediates or transition states shown in Scheme 1. It might look far-fetched to think that the exchange (and isomerization) model based on formation of M-M' interactions at short distances could be found for less similar metal centers, but the fact is that in our theoretical mechanistic studies on the ZnMe2-catalyzed cis/trans isomerization of [PdMeAr(PR3)2] complexes (Ar = C6Cl2F3 and C6F5) we found Zn II playing a structural role quite similar to that of Au I in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…The complexes showing aurophilic (Au ··· Au) interactions have been widely studied . Other than Au I , metal ions such as Ag I , Hg II , Cu I , Pd II , Pt II , Ga I , In I , Tl I are also known to involve in homo‐/hetrometallic metallophilic interactions …”
Section: Introductionmentioning
confidence: 99%